2020
DOI: 10.1039/d0nj00016g
|View full text |Cite
|
Sign up to set email alerts
|

Electrode processes in the KF–AlF3–Al2O3 melt

Abstract: SEM-EDX image of the oxide layer on the surface of the 90Cu–Al anode after the electrolysis process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Padamata et al performed electrolysis in VEC using Cu 90 Al 10 anode and tungsten cathode in alumina-saturated KF-AlF 3 melt (with CR 1.4) at 800 °C. 26 The cell voltage was stable for the first 4 h, however, the voltage increased from 4.2 to 5.8 V in the next 14 h. The increase in the cell voltage could be due to an increase in oxide scale thickness during the electrolysis (oxide scale thickness ≈ 140 μm) or the presence of CuF 2 scale between the anode and the oxide scale. The current efficiency of the process was 84.1%, and the aluminium purity was 99.4%, where the main impurities were Si (0.157 wt%), Fe (0.253 wt%) and Cu (0.0984 wt%).…”
Section: Inert Anode Materialsmentioning
confidence: 91%
“…Padamata et al performed electrolysis in VEC using Cu 90 Al 10 anode and tungsten cathode in alumina-saturated KF-AlF 3 melt (with CR 1.4) at 800 °C. 26 The cell voltage was stable for the first 4 h, however, the voltage increased from 4.2 to 5.8 V in the next 14 h. The increase in the cell voltage could be due to an increase in oxide scale thickness during the electrolysis (oxide scale thickness ≈ 140 μm) or the presence of CuF 2 scale between the anode and the oxide scale. The current efficiency of the process was 84.1%, and the aluminium purity was 99.4%, where the main impurities were Si (0.157 wt%), Fe (0.253 wt%) and Cu (0.0984 wt%).…”
Section: Inert Anode Materialsmentioning
confidence: 91%
“…Moreover, the temperature of the process can be lowered to 700-850 °C by replacing sodium cryolite with low-temperature fluoride or chloride melts with considerable solubility of Al2O3. The promising option, the molten 1.3KF-AlF3 system has been studied elsewhere [89][90][91]. This process is patented [92] and now is under the laboratory scale studies [93] While Pt is successfully concentrated in the alloy, Re requires additional effort to be extracted as it is oxidized in a wide range of temperatures.…”
Section: One-step Methodsmentioning
confidence: 99%
“…It is also stressed that metal fluoride is formed between the oxide layer and the metal during longer duration electrolysis at high current densities due to the oxide ion depletion in the infiltrated electrolyte. This phenomenon was studied in [15] and it was found that metal ions are reduced from this metal fluoride layer on the inner side of the oxide layer. An SEM image showing the presence of metallic copper on the inner side of the oxide layer removed from the 90Cu10Al anode after long term polarization is shown in Fig.…”
Section: Mechanisms Of Anode Corrosion and Aluminium Contaminationmentioning
confidence: 99%
“…The same can occur at different quasi-inert anodes at proper potentials. However, significant diffusion limitations were observed in [15] where limiting current densities were as low as 0.3-0.8 A/cm 2 in KF -AlF3 melts at 750-850 °C.…”
Section: Mechanisms Of Anode Corrosion and Aluminium Contaminationmentioning
confidence: 99%
See 1 more Smart Citation